Investigating Secondary Special Educator’s Perception of Interagency Collaboration - Li, Jen Yi; Lin, Hsintai (Journal of the American Academy of Special Education Professionals, 2009)
This paper addresses the development and validation of the Interagency Collaboration Scale (ICS), a 17-item self-report measure that investigates secondary special educators’ perceptions of interagency collaboration. An exploratory factor analysis was conducted on data from a sample (N = 260) of secondary special educators who are members of the Council for Exceptional Children. The results revealed a 4-factor solution as the most interpretable factor pattern. These four factors were: Importance of Interdisciplinary Collaboration, Collective Ownership of Goals, Newly Created Professional Activities, and Evaluation on Collaborative Process. The reliability estimates were acceptable from 0.76 to 0.83. The factor structure was recovered in a confirmatory factor analysis conducted on a second, independent sample (N = 343). Limitations and Implication were discussed.